2018
DOI: 10.1021/acs.jpcc.8b01011
|View full text |Cite
|
Sign up to set email alerts
|

Electron–Phonon Coupling in Luminescent Europium-Doped Hydride Perovskites Studied by Luminescence Spectroscopy, Inelastic Neutron Scattering, and First-Principles Calculations

Abstract: We present a case study on the vibrational coupling of lattice phonons to the electronic 4f 7 ( 8 S 7/2 ) -4f 6 5d 1 (e g ) transition of divalent europium in the hydrides and deuterides LiMH 3 and LiMD 3 (M = Sr, Ba). For low doping concentrations, these compounds show extraordinarily well-resolved vibronic fine structures at low temperatures.Besides luminescence emission spectroscopy of the europium-doped compounds, we carried out inelastic neutron scattering experiments of the europium-free compounds.The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…120 K the spectra started to show a well‐resolved vibronic fine structure. The vibrational features were assigned to different modes and their overtones and, for comparison, inelastic neutron scattering of the Eu 2+ ‐free compounds was carried out, the spectra were compared to simulated spectra from density functional calculations and a good agreement was observed . A comparison of the vibrational modes in the excitation and emission spectra yielded the information that the binding strength of the Eu–H‐bond becomes weaker in the Eu 2+ 5d (e g ) excited state.…”
Section: Eu2+‐doped Hydridesmentioning
confidence: 98%
“…120 K the spectra started to show a well‐resolved vibronic fine structure. The vibrational features were assigned to different modes and their overtones and, for comparison, inelastic neutron scattering of the Eu 2+ ‐free compounds was carried out, the spectra were compared to simulated spectra from density functional calculations and a good agreement was observed . A comparison of the vibrational modes in the excitation and emission spectra yielded the information that the binding strength of the Eu–H‐bond becomes weaker in the Eu 2+ 5d (e g ) excited state.…”
Section: Eu2+‐doped Hydridesmentioning
confidence: 98%
“…We note however that some previous vibronic studies, mixing experimental and theoretical analysis, were already carried out. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…For the past decades, hydrides and mixed anion hydrides containing Eu 2+ dopant have been reported to exhibit green-red luminescence. 10,[14][15][16][17][18][19][20] However, their poor stability in air and moisture limits their application. In contrast, we have recently demonstrated that oxyhydride GdHO is stable in ambient air and can act as a phosphor host for Tb 3+ .…”
Section: Introductionmentioning
confidence: 99%